PRESSURE CHANGES IN MEDIA MAINTENANCE OF SHELL PEARL (Pinctada maxima) LARVAE ON PROTEASE ENZYME ACTIVITY ENHANCING GROWTH AND SURVIVAL - M.S. Hamzah (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2015)
The growth of pearl shell oyster is influenced by nacre availability consisting of calcium carbonate. Nacre is identified as a protein metabolism product in pearl oyster. The aim of this study was to evaluate the effects of media level pressure in larva rearing tank on protease enzyme activity to promote growth performance and survival rate of Pinctada maxima larvae. The research was conducted from March 6th to May 7th 2015 in laboratorium of Mataram Marine Bio Industry Technical Implementation Unit, LIPI. “Chi-Square” test showed that survival rate of larvae at Umbo-veliger stage (planktonic) was significantly affected by water level pressure within 99% with ratio 1.00:1.61. In contrast, treatment with no water level pressure also significantly influenced the survival rate of larvae in spat stage within 99% confidence with ratio of 1.00:1.93. The highest average survival rate of larvae in umbo-veliger and spat stages were 13.10% and 2.60%, respectively. The effect of protease enzyme activity on calcium carbonate production to produce oyster shell are also discussed in this paper. Keywords:  water level pressure, protease enzyme activity, survival rate, growth, larvae, P. maxima